Respiratory Failure Secondary to Human Metapneumovirus Requiring Extracorporeal Membrane Oxygenation in a 32-Month-Old Child - Abha Gupta; Melania Bembea; Anna Brown; Courtney Robertson; Lewis Romer; Ronald D. Cohn (Case Reports in Pediatrics)
Human metapneumovirus (HMPV) is a common virus that can cause respiratory problems ranging from mild upper respiratory tract disease to respiratory failure requiring mechanical support. Here, we report a case of a 32-month-old male with a previous history of asthma, who developed respiratory failure two weeks after onset of cough and rhinorrhea and required extracorporeal membrane oxygenation (ECMO) for 9 days after failing high-frequency oscillatory ventilation (HFOV). To our knowledge, this is the oldest reported pediatric patient with respiratory failure secondary to human metapneumovirus that did not respond to mechanical ventilation. This case highlights three critical points: the potentially fatal causative role of HMPV in respiratory failure in an older pediatric age group of immunocompetent hosts, the importance of early recognition of impending respiratory failure, and the timely utilization of ECMO.